2020
DOI: 10.3390/ijms21176265
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids and Prostate Cancer: A Systematic Review of Animal Studies

Abstract: Prostate cancer is a major cause of death among men worldwide. Recent preclinical evidence implicates cannabinoids as powerful regulators of cell growth and differentiation, as well as potential anti-cancer agents. The aim of this review was to evaluate the effect of cannabinoids on in vivo prostate cancer models. The databases searched included PubMed, Embase, Scopus, and Web of Science from inception to August 2020. Articles reporting on the effect of cannabinoids on prostate cancer were deemed eligible. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 63 publications
0
23
0
Order By: Relevance
“…It has been shown that CBD has multiple pharmacological benefits in in vitro and animal studies, which makes it a very promising therapeutic commodity in inflammation, diabetes, cancer, and neurodegenerative diseases [ 34 , 35 ]. It is demonstrated that CBG has a promising therapeutic potential in the treatment of inflammatory bowel disease and prostate cancer [ 35 , 36 ]. An early study by Mahlberg and Hemphil showed the higher level of THC in cannabis leaves grown under sunlight than the plants grown under filtered green light and darkness while there was no significant difference in THC content in plants grown under filtered blue and red lights and shaded daylight compared to the sunlight grown plants [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that CBD has multiple pharmacological benefits in in vitro and animal studies, which makes it a very promising therapeutic commodity in inflammation, diabetes, cancer, and neurodegenerative diseases [ 34 , 35 ]. It is demonstrated that CBG has a promising therapeutic potential in the treatment of inflammatory bowel disease and prostate cancer [ 35 , 36 ]. An early study by Mahlberg and Hemphil showed the higher level of THC in cannabis leaves grown under sunlight than the plants grown under filtered green light and darkness while there was no significant difference in THC content in plants grown under filtered blue and red lights and shaded daylight compared to the sunlight grown plants [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“… 29 On the contrary, cannabinoid agonists induced apoptosis of PCa cells and reduced the size of tumors. 12 , 13 Additionally, several in vivo and in vitro studies revealed the crucial role of cannabinoid receptors in the anti‐proliferation of BCa cells. 27 , 30 …”
Section: Discussionmentioning
confidence: 99%
“…Several functional studies elaborated that cannabinoids appeared to inhibit cell proliferation, migration, and angiogenesis in urological cancer cells. 11 , 12 , 13 …”
Section: Introductionmentioning
confidence: 99%
“…The lack of knowledge of how cannabis exerts its anticancer effects makes it even more complicated to find what is the best way these compounds can be used without these psychoactive effects. However, there is enough evidence in the literature stating the ability of cannabinoids to induce cell death by various pathways in prostate cancer, but there is still more research needed to be undertaken to understand their mechanism [104,105]. Although cannabinoids may well be able to help with management of prostate cancer, there is still an urgent need to identify the best and the most effective combination for these and other cancers.…”
Section: Discussionmentioning
confidence: 99%